Commensal Flora, is it an Unwelcomed Companion as a Triggering Factor of Autoimmune Pancreatitis? - Haruta, Ikuko; Shimizu, Kyoko; Yanagisawa, Naoko; Shiratori, Keiko; Yagi, Junji (Frontiers in Physiology, 2012)
The etiopathogenesis of many autoimmune disorders has not been identified. The aim of this paper is to focus on the involvement of bacterial exposure, as an environmental factor, in the pathogenesis of autoimmune pancreatitis (AIP), which is broadly categorized as autoimmune disorders involving pancreatic lesions. Avirulent and/or commensal bacteria, which may have an important role(s) as initiating/progressing factors in the pathogenesis of autoimmune disorder AIP, will be emphasized.